Effect of fertilizer levels and supplementary irrigation on late maturing transplanted paddy under rainfed medium land situations - Mohanty, S; Rautaray, S K; Panda, D K (ORYZA-An International Journal of Rice, 2018)
A field experiment was conducted at the Research Farm of Indian Institute of Water Management (IIWM), Bhubaneswar in the kharif season for two years (2012 and 2013) to study the effect of supplementary irrigation and fertilizer levels on long duration paddy variety ’Swarna’ grown in a medium land having dyke height of 20 cm around the plots. Dry spells of 18 to 21 days duration occurred at panicle initiation and flowering stage in the first year, and at active tillering and panicle initiation stage in the second year. The results revealed that as compared to the rainfed situation, two supplementary irrigations (5 cm each using flexi pipe) during the dry spells (at active tillering, panicle initiation and flowering stages) improved rice grain and straw yield by 15.7% and 10.3%, respectively. Recommended fertilizer dose (80 kg N, 40 kg P2O5 and 40 kg K2O ha-1) increased rice grain and straw yields by 18.2% and 16.1%, respectively, as compared to the 60% of the recommended dose.